2022
DOI: 10.5852/ejt.2022.806.1699
|View full text |Cite
|
Sign up to set email alerts
|

The tornoceratid ammonoids from the Roteisenstein Formation of Dillenburg (Cephalopoda, Ammonoidea)

Abstract: The ammonoids of the suborder Tornoceratina from the Middle to Late Devonian Red Ironstone Formation of the area around Dillenburg (eastern Rhenish Mountains) are revised, mainly based on historical collections stored in the Museum für Naturkunde, Berlin. The species Tornoceras typus (Sandberger & Sandberger, 1851), Tornoceras frechi Wedekind, 1918 and Epitornoceras mithracoides (Frech, 1888) are re-described based on the original material from the Red Ironstone. The new genus Lentitornoceras gen. nov. is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the meantime, two monographs on the ammonoids of the Red Ironstone have been published; these dealt with the suborders Pharciceratina (Korn & Bockwinkel 2021) and Tornoceratina (Korn & Bockwinkel 2022). In a third step of the revision, we here present the re-description of the ammonoids of the suborder Gephuroceratina, of which eight species are described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, two monographs on the ammonoids of the Red Ironstone have been published; these dealt with the suborders Pharciceratina (Korn & Bockwinkel 2021) and Tornoceratina (Korn & Bockwinkel 2022). In a third step of the revision, we here present the re-description of the ammonoids of the suborder Gephuroceratina, of which eight species are described.…”
Section: Discussionmentioning
confidence: 99%
“…The stratigraphic occurrence of the species of the suborder Pharciceratina has already been discussed by Korn & Bockwinkel (2022). There, it was concluded that these forms originate from three intervals, in ascending order: (1) Maenioceras terebratum Zone, (2) Pseudoprobeloceras pernai Zone and (3) Sandbergeroceras costatum Zone.…”
Section: Ammonoid Stratigraphymentioning
confidence: 96%
“…The genus Kornia was introduced by for very small specimens which are characterised by their spindle-shaped conch and conspicuous umbilical shape, thus differing strongly from all other known early Tournaisian ammonoids. Juvenile ammonoids with such a shape, however, occur repeatedly in the fossil record, as shown for the Late Viséan genera Goniatites de Haan, 1825 (Klug et al 2016;Korn 2017) and Hibernicoceras Moore & Hodson, 1958(Schmidt 1925Korn 1988a).…”
Section: Remarksmentioning
confidence: 93%
“…In the Treatise revision, Kullmann (2009) expressed a view of the family Gattendorfiidae that is clearly different from previously published concepts (Bartzsch & Weyer 1987, 1988aKorn 1994;. His scheme differs, on the one hand, in that the gattendorfiid and pseudarietitid clades are not considered as sister groups and, on the other hand, in that genera such as Acutimitoceras and Stockumites are also placed in the family Gattendorfiidae.…”
Section: Remarksmentioning
confidence: 98%
See 1 more Smart Citation